Integrity of Discourse in the Radar Sulawesi Barat Daily Newspaper : The Use of Cohesion and Coherence in Learning Indonesian to Improve Students' Literacy and Knowledge Skills - Idris Idris; Al Fandi; Moh Tahir; Gusti Ketut Alit Suputra; Syamsuddin Krida (Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This study aims to analyze cohesion and coherence in forming the wholeness of the discourse contained in the Radar Sulawesi Barat daily. This research was qualitative. The data was collected using listening and note-taking techniques with several stages: reading, marking, and classifying. The data obtained in this study were written as elements that made up the wholeness of the discourse. The method and technique of data analysis used was the intralingual equivalent method with the comparison technique of equating the main points. Based on the study's results, cohesion and coherence shape the wholeness of discourse in the Radar Sulawesi Barat daily. Discourse cohesion found in this study was a marker of grammatical and lexical cohesion. Grammatical cohesion markers include (1) references, (2) substitutions, and (3) conjunctions. Lexical cohesion markers are repetition; the repetition obtained consists of (1) complete repetition, (2) repetition with changes in form, (3) repetition with changes, (4) repetition with synonym changes, and (5) repetition with hyponyms. In addition to repetition, a marker of lexical cohesion was also found, namely collocation. Furthermore, the element that forms the wholeness of discourse was coherence. This study had a meaning or semantic relationship between elements or sentences in the discourse, which can be used as a strategy for learning Indonesian.